Whiplash injury and neuro-otological sequelae: An evidence based systematic review. (June 2014) - Samji, Alim; Thiagarajan, Venkataramana; Yeoh, Robin
Abstract Objective: Epidemiological data showing an association between whiplash and neuro-otological symptoms have existed for many years; however, despite growing evidence a causal relationship has not been forthcoming. This review aims to identify whether evidence exists to substantiate a pathophysiological link between whiplash and its presumed neuro-otological consequences. Study design: A literature search was performed in accordance with 'the literature search process: guidance for NHS researchers', using the search terms 'whiplash', 'vertigo', 'hearing loss', 'dizziness', 'tinnitus', 'hyperacusis'. This was augmented using citation linking. Results: No evidence was found that satisfactorily proved a pathophysiological link, but there was evidence to support several plausible theories. For hearing loss and tinnitus/hyperacusis these include auditory processing disorders (APD) secondary to cerebral hypoperfusion due to stimulation of cervical nociceptive afferents; and Eustachian tube dysfunction secondary to temporomandibular joint dysfunction. For vertigo/dizziness they include 'cervical dizziness' secondary to damage to vestibulocollic/cervicocollic reflexes, osteoarticular tendon sensors/cervical neuromuscular spindles with resulting proprioceptive dysfunction and discordance with visual input; central or peripheral vestibular pathology; and psychosocial factors. Conclusions: The results highlight the multifactorial, biopsychosocial nature of whiplash. Although the largest contributors to neuro-otological symptoms appear to be psychosocial, the results identify promising, if largely theoretical, pathophysiological mechanisms. Unfortunately, much of the work is underpowered and often lacks controls. It therefore creates a need for further research and forms a basis for that research.